Combined effects of artificial sweetener acesulfame on the uptake of Cd in rice (Oryza sativa L.). (September 2019) - Xu, Yali; Li, Ke; Liu, Yubin; Liu, Zhen; Wang, Lei; Pu, Jian; Xu, Zhen; Sun, Hongwen
Abstract: Organic pollutants are widely detected in surface water, groundwater and irrigation sewage in farmland soil, some of which can form complexes with heavy metal ions as ligands in the environment. Acesulfame (ACE), one of the most popular artificial sweeteners, has been found in wastewater sometimes at tens of microgram per liter. However, the combined effects of heavy metals and ACE are still unclear. In the present study, the effects of ACE on cadmium (Cd) absorption and translocation in rice seedlings ( Oryza sativa L.) under different exposure conditions were investigated using hydroponic experiments. Under the combined exposure treatments of ACE and Cd, absorption of Cd and ACE in rice significantly decreased when compared with the single exposure treatments, while the alleviation of oxidative damage in rice was also found. Under the sequential exposure treatments of Cd and ACE, the post-exposed ACE activated the pre-absorbed Cd in plant, and accelerated the release of Cd to the environment as well as its translocation from the roots to shoots. In addition, compared with the single Cd exposure, the accumulated ACE can alleviate the oxidative damage in rice shoots induced by Cd, although the Cd concentrations in shoots changed little. In summary, the combined pollution of artificial sweetener ACE was beneficial to relieve the toxicological damage and ecological risk caused by Cd. Graphical abstract: Image 1 Highlights: Combined ACE exposure decreased the Cd accumulation and translocation in rice. Subsequent ACE exposure promoted the translocation and release of pre-absorbed Cd. Translocation of ACE in rice was high, which can be reduced by jointly Cd exposure. Cd-induced root damage and antioxidant enzyme activity were alleviated by ACE. Abstract : This work provided a new perspective for combined pollution of heavy metals and emerging organic contaminants with ligand capability.